Study of Handloom Development Programme - Planning Commission (Planning Commission, 1967)
Till the advent of the machine age revolutionising the production of textile goods, the handloom industry in India was playing the most important role in the country’s economy. It was, and even now is the largest cottage industry of the country. Nearly a third of the total requirement of cloth is provided from this industry. India has a rich past in the handloom industry; the country used to export handloom textiles of excellent quality to Middle East and European Countries. With the growth of textile mills, the handloom industry started facing competition from them.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission